Measuring the effectiveness of salespeople: Evidence from a cold-drink market - Haofeng Jin; Zhentong Lu (Bank of Canada, 2021)
Salespeople are widely employed in many industries and are perceived as an effective marketing strategy. However, due to lack of field data, direct empirical evidence on the effectiveness of salespeople is scarce. In this paper, leveraging a unique retail sales data set from a leading Chinese cold-drink manufacturer and information on its implemented salespeople assignment rule, we measure the causal effect of salespeople on product revenue. Our estimation strategy features a non-linear control function approach to address the endogeneity problem in salespeople assignment by exploiting the manufacturer's internal allocation rules. Our results show that the marginal effect of the first salesperson is 16.2 percent and that of the second is 10.6 percent. We provide some evidence on the incentive issues caused by the manufacturer's compensation plan as a possible explanation for the decreasing effect of an additional salesperson.
Keywords: L81; M3; M5; 330; Labour markets; Service sector